PENGARUH KOMBINASI 2,4-D DAN BENZIL AMINO PURIN (BAP) TERHADAP PEMBENTUKAN KALUS PADA EKSPLAN DAUN KENCUR (Kaemferia galangal L) SECARA IN VITRO - Anis Shofiyani; Agus Mulyadi Purnawanto (Universitas Muhammadiyah Purwokerto, 2010)
This research aim to learn the influence of combination of concentration plant growth regulator 2,4-D and BAP to callus induction at eksplan of Koempheria galanga leaf, proliferasi callus at eksplan and also know the interaction influence between 2,4-D and BAP to obtaining culture of callus Koempheria galanga which its growth good. This research was conducted from April to September 2010, in Laboratory of Tissue Culture, FKIP, University of Muhammadiyah Purwokerto. The Trial was arranged in Complete Random Design (CRD). Perception variable cover the : time induce the callus, percentage explant growth, callus volume which grow from explants leaf , culture appearance visually and percentage contamination. Result of research indicate that the Combination of concentration of Plant growth regulator 2,4-D at concentration 0 - 2 mg / l of medium and BAP at] concentration 0 - 0,3 mg / l medium still not yet able to induce formed is callus at eksplan of leaf Koempheria galanga during research. Disability Explants form the callus because of fenol high rate enough in tissue explant and also not yet proportional it concentration 2,4 D and Benzil Aminopurin which can depress the sintesis fenol in and death at explant of koempheria galanga leaf.